واقع تطبيق إدارة المعلومات التسويقية في الشركات: شركة كريم السعودية أنموذجاً - الأنصارى، لال عبدالقادر; الرابغي، ريم علي محمد (الاتحاد العربى للمكتبات والمعلومات, 2019)
تناولت الدراسة واقع تطبيق إدارة المعلومات التسويقية في الشركات، وناقشت كافة جوانب الموضوع من أهمية، وأهداف، ووظائف إدارة المعلومات التسويقية وفق رؤية السعودية 2030، وحددت مشكلة الدراسة في التساؤل الرئيس: ما هو واقع تطبيق إدارة المعلومات التسويقية في شركة كريم السعودية ؟، وركزت أهدافها على دراسة واقع تطبيق إدارة المعلومات التسويقية في شركة كريم السعودية، والمعوقات التي تحول دون ذلك، بالإضافة إلى قياس مدى فعالية تطبيق إدارة المعلومات التسويقية في الشركة من وجهة نظر موظفي قسم التسويق، ولتحقيق تلك الأهداف تم استخدام المنهج الوصفي التحليلي، مع استخدام أسلوب دراسة الحالة، ولجمع المعلومات فقد اعتمدت الدراسة على أداتين، تمثلت الأولى في أداة المقابلة المقننة وتوجيهها إلى مدير التسويق العام بشركه كريم السعودية، فيما تمثلت الثانية في أداة الاستبانة وتوجيهها إلى جميع موظفي قسم التسويق في الشركة والبالغ عددهم (10) أفراد يمثلون كامل مجتمع الدراسة، وأظهرت الدراسة عددا من النتائج أهمها: أن واقع تطبيق وظائف إدارة المعلومات التسويقية في الشركة جاءت بدرجة تطبيق (دائما) بشكل عام، فيما كشفت الدراسة أن موظفي التسويق لا يوافقون على وجود معوقات لتطبيق إدارة المعلومات التسويقية في الشركة بشكل عام، إلا أن هناك بعض المعوقات التي أشاروا إليها، من أبرزها قلة مصادر المعلومات التسويقية، كما أظهرت الدراسة أن موظفي التسويق يرون من وجهة نظرهم أن قياس تطبيق إدارة المعلومات التسويقية في الشركة تمتاز بالفعالية العالية، وأوصت الدراسة بضرورة أن تتبنى الشركة استحداث قسم وظيفي يدرج في الهيكل التنظيمي لقسم التسويق تحت مسمى "إدارة المعلومات التسويقية"، وضرورة أن ينظر قسم التسويق في الشركة إلى المعوقات التي تحول دون تطبيق إدارة المعلومات التسويقية والسعي لإيجاد حلول لها، مع إجراء متابعة دورية أثناء تطبيقها، بالإضافة إلى ضرورة توفير دورات تدريبية وورش عمل لموظفي التسويق الحاليين؛ لرفع كفاءتهم وقدراتهم المعلوماتية بشكل عام، لا سيما فيما يتعلق بأساليب وطرق البحث عن المعلومات التسويقية، مع السعي للحصول على كوادر مؤهلة ومتخصصة أكثر في مجالي التكنولوجيا والمعلومات.
The study tackled the reality of marketing information management in companies dealing with all aspects of the subject including the importance, aims, and functions of marketing information management according to Saudi Vision 2030. The study problem lied in the following main question: "What is the reality of applying marketing information management in Saudi Careem Co.?" Its objectives focused on studying the reality of applying marketing information management in Careem and the obstacles hinders such application besides measuring the effectiveness of applying marketing information management in the company from viewpoints of marketing department staff. To achieve these objectives, Was used descriptive analytical approach and method of case study. The study was based on two tools for collecting information; the first is the codified interview addressed to directors general of marketing in the company. The second tool is a questionnaire addressed to the staff of marketing department in the company; (10) individuals representing complete community study. The study revealed several findings including: the reality of applying marketing information management in the company came in "Always" degree in general. The study showed that staff of marketing department do not agree that there are obstacles against applying marketing information management in the company in general. However, they stated certain obstacles such as lack of marketing information sources. In addition, the study revealed that most marketing staff members think that marketing information management in the company is highly. The study recommended the company to develop a new section in the organizational structure namely "Marketing Information Management" in marketing department. Marketing Dept. is to consider the obstacles hindering the application of marketing information management and seek for solution as well as the regular follow up during application. The study also recommended the necessity to provide training courses and workshops to current marketing staff in order to increase their sufficiency and informational abilities in general and with regard to research and getting marketing information in particular. The company also is to look for specialized and qualified human resources in technology and information
Keywords: المعلومات التسويقية -- إدارة المعلومات التسويقية -- شركة كريم السعودية -- رؤية السعودية 2030